2009
DOI: 10.1063/1.3180819
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-helium snowball complexes formed on helium nanodroplets

Abstract: We systematically investigate the formation and stability of snowballs formed by femtosecond photoionization of small alkali clusters bound to helium nanodroplets. For all studied alkali species Ak=(Na, K, Rb, Cs) we observe the formation of snowballs Ak + HeN when multiply doping the droplets. Fragmentation of clusters AkN upon ionization appears to enhance snowball formation. In the case of Na and Cs we also detect snowballs Ak + 2 HeN formed around Ak dimer ions. While the snowball progression for Na and K … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 37 publications
7
56
3
Order By: Relevance
“…Using this procedure the first solvation shell is found to host 19.2 (21.4) atoms for Rb + (Cs + ). These values are somewhat larger than those found experimentally [32,34] and by QMC calculations [3]. Figure 3 shows the equilibrium configuration of Ba + @ 4 He 1000 .…”
Section: A Staticscontrasting
confidence: 44%
“…Using this procedure the first solvation shell is found to host 19.2 (21.4) atoms for Rb + (Cs + ). These values are somewhat larger than those found experimentally [32,34] and by QMC calculations [3]. Figure 3 shows the equilibrium configuration of Ba + @ 4 He 1000 .…”
Section: A Staticscontrasting
confidence: 44%
“…135, 074306 (2011) in Ref. 15. The observation of large Rb + -He N aggregates (N > 1000) with Rb + in a He snowball configuration inside a He nanodroplet was recently reported.…”
Section: Introductionmentioning
confidence: 90%
“…Mixed quantum/classical dynamics calculations and, more recently, density functional theory studies identified the linear triatomic He + 3 ion as the centre of an isolated snowball cluster 14,15 , which should have an effect on the mobility 16 . The picture of a solid snowball forming around a positive core was also found valid for foreign ions and has received both experimental and theoretical support: on the experimental side the long life-time of nuclear spin polarised 12 B + and 8 Li + ions injected into liquid helium 17 has been attributed to helium snowballs forming around the positively charged foreign ion; the observation of magic numbers in the time-of-flight mass spectrum of He n Cs + and He n Ar + clusters ejected from large doped helium droplets 18,19 showed the prevalence of specific -hence solid -structures; on the theoretical side, Diffusion Monte Carlo (DMC) calculations for small 4 He clusters containing alkali ions revealed solid-like snowballs surrounded by a liquid-like environment of additional solvent atoms [20][21][22] . Also radial density profiles from DMC calculations for Pb 2+ He n for several relevant sizes n show peak helium density values much higher than the density of solid helium 23 .…”
Section: Introductionmentioning
confidence: 92%